From Stárets Zosima to Aliosha Karamázov: Dostoevsky and his Model of ‘New Man’ - Escobar Torres, Miguel (Contrastes. Revista Internacional de Filosofía, 2021)
In this paper I trace back the origins of Dostoevsky’s spirituality, following an almost continuous line from the Desert Fathers to the startsí in the Russia of the XVIII-XIX centuries. During this period, I study the consequences of the XV century controversy between Nil Sorsky and Iósif Volotsky, which will configure the two main spiritual lines that will mark the Russian thought. I sustain that Dostoyevsky follows the spiritual current founded by Nil Sorsky, received from the reading of the works of Tikohn Sadonsky, as well as from his encounters with the Stárets Amvrosy in Optina, on whom he finds inspiration to create the figure of Stárets Zosima. Finally, I maintain that Dostoevsky breaks the walls of the convent to propose the flourishing of a new model of ‘New Man’, embodied in Aliosha Karamázov.